Fiscal Monitor, November 2010 : Fiscal Exit: From Strategy to Implementation - Gerson, Philip (Fiscal Monitor; Fiscal Monitor ;, 2010)
With increasing fiscal challenges in the aftermath of the global financial crisis, multilateral surveillance of fiscal developments, a key part of the IMF's surveillance responsibilities, has gained further importance. In response, the Fiscal Monitor was launched in 2009 to survey and analyze the latest public finance developments, update fiscal implications of the crisis and medium-term fiscal projections, and assess policies to put public finances on a sustainable footing. The Fiscal Monitor is prepared twice a year by the IMF's Fiscal Affairs Department. The Monitor's projections are based on the same database used for the October 2010 World Economic Outlook (WEO) and Global Financial Stability Report.